2016
DOI: 10.1007/s00270-016-1412-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Occlusion of Large Extra-Prostatic Anastomoses During Prostatic Artery Embolization for Symptomatic BPH

Abstract: PAE using the protection technique in case of large extra-prostatic shunts is as safe and effective as basic procedures and does not induce any additional time of procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
5
22
1
Order By: Relevance
“…In a study of 11 patients, Amouyal et al (60) found penile or rectal shunts in 10% of catheterized PAs. Coils were placed distal to prostate branches and close to the extraprostatic anastomosis.…”
Section: Coil Embolizationmentioning
confidence: 98%
“…In a study of 11 patients, Amouyal et al (60) found penile or rectal shunts in 10% of catheterized PAs. Coils were placed distal to prostate branches and close to the extraprostatic anastomosis.…”
Section: Coil Embolizationmentioning
confidence: 98%
“…Although coils are most commonly used, Gelfoam use has also been reported in the literature. 20 If anastomosis is inaccessible, it is recommended to use intraprostatic vasodilators combined with very slow injection of particles. 21 After such maneuvers, the anastomoses are usually no longer visualized; however, they become more evident when the peripheral resistance increases, after saturation of prostatic vascular bed by particles.…”
Section: Discussionmentioning
confidence: 99%
“…These may be seen in 10 to 20% of patients. 30,31 However, a distinction must be made between small and large extraprostatic shunts. The former is frequently not visible on DSA unless a high-powered injection is employed.…”
Section: Embolizationmentioning
confidence: 99%
“…In the context of slow-flow embolization utilized in PAE, nontarget delivery of particles to these vessels is not encountered due to preferential flow to the prostate. 20,30 In the case of larger shunts that are visible on DSA or low-pressure injection, these may either be avoided through advancement of the microcatheter distal to their takeoff or with coil embolization. The vessels at risk of nontarget embolization have been described extensively elsewhere, 30 and include superior vesicle, rectal, and pudendal branches.…”
Section: Embolizationmentioning
confidence: 99%
See 1 more Smart Citation